EFFECT OF N-TRIACONTANOL ON THE GROWTH OF SALT STRESSED SOYBEAN PLANTS - R Radha Krishnan,; B D Ranjitha Kumari, (Tropical Life Sciences Research, 2008)
The present investigation was made to describe the effect of foliar application of n-triacontanol on plant growth, physiological and biochemical parameters in soybean under sodium chloride (NaCl) stress. The seeds were propagated into the soil supplemented with 10, 15, 20, 25 and 30 mM NaCl. A moderate reduction of plant growth was observed in 20 mM NaCl treatment compared to other concentration of NaCl treatments. Hence, the n-triacontanol was sprayed on the plants grown under the 20 mM NaCl added soil. Increased in specific leaf area (SLA), leaf weight ratio, relative water content and decreased in leaf osmotic potential were noted in n-triacontanol treated plants than that of salt stressed untreated plants. Moreover, the chlorophyll pigments, nucleic acids, total soluble sugars and proteins were also found to be increased in the n-triacontanol treated plants. The accumulation of proline was decreased in salt stressed plants that had been treated with n-triacontanol. The present study effectively proved that n-triacontanol was able to restore the normal metabolic process in the salt stressed soybean.